2002
DOI: 10.1034/j.1600-0897.2002.1o027.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the Uterus of Mice with Pregnancy Loss

Abstract: Our results suggest a possible role for the apoptotic process in mechanisms mediating pregnancy loss and indicate an involvement of p53 and bcl-2 in its regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…Increasing studies have demonstrated that RSA is associated with a high level of cell apoptosis [18] . As a well-known inducer of cell apoptosis [19] , the Pro polymorphism of codon 72, which affects the activity of p53, may serve as a susceptibility factor of RSA [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have demonstrated that RSA is associated with a high level of cell apoptosis [18] . As a well-known inducer of cell apoptosis [19] , the Pro polymorphism of codon 72, which affects the activity of p53, may serve as a susceptibility factor of RSA [11] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteins involved in trophoblastic invasion and angiogenesis have been identified. One such protein is p53, a tumor suppressor, a potent inducer of apoptosis and angiogenesis [5]. Low expression of apoptosis and angiogenesis related genes have been associated with implantation failure [3].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of MMPs at the implantation site is stimulated by the serine protease plasmin, the production of which is regulated by plasminogen activator inhibitors (PAI) (5). The p53 tumor suppressor gene is a potent inducer of apoptosis, regulates cell growth, and induces angiogenesis (6,7). Vascular endothelial growth factor (VEGF) is the best characterized regulator of angiogenesis (8).…”
mentioning
confidence: 99%